Assessment of dry etching damage in permalloy thin films - Kim, SD; Lee, JJ; Lim, SH; Kim, HJ (AMER INST PHYSICS, 1999)
Permalloy (Ni81Fe19) thin films are etched by ion beam etching (IBE) or reactive ion etching (RIE), and the variation of magnetic properties with etching time is investigated. Magnetic softness of permalloy thin films deteriorates as etching proceeds, i.e., film thickness decreases. Coercivity begins to increase steeply at a thickness of 0.4 mu m and reaches 16 Oe for IBE and 8 Oe for RIE at 0.09 mu m. Effective magnetization is increased by 0.2 kG with IBE but decreased by 0.7 kG with RIE. From an atomic force microscopy analysis and independent wet etching experiments, the increase of coercivity is proved to be attributed to the increase of surface roughness as a result of etching. Etching-induced defects are also responsible for the increase of coercivity, which is confirmed by a measurement of electrical resistivity and x-ray diffraction analysis. Ion beam etching process appears to affect magnetic properties to a greater extent than reactive ion etching process. (C) 1999 American Institute of Physics. [S0021-8979(99)54608-2].